Histological Compatibility in Distal Neurotizations: A Systematic Review - Cavalheiro, Cristina Schmitt; Nakamoto, João Carlos; Wei, Teng Hsiang; Sorrenti, Luiz; Wataya, Erick Yoshio (Indian Journal of Plastic Surgery, 2023)
Considering the importance of defining the minimum number of axons between recipient and donor branches, that is, the definition of histological compatibility in distal neurotizations for the success of the procedure and the surgeon's freedom to choose individualized strategies for each patient, this systematic review was conducted to find out the most recent studies on the subject. The objective of this systematic review was to determine the importance of the number of axons and the relationship between axon counts in the donor and recipient nerves in the success of nerve transfer. A literature review was performed on five international databases: Web of Science, Scopus, Wiley (Cochrane Database), Embase, and PubMed. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines were followed (2020 version), a guide designed to guide the elaboration of systematic literature reviews. One hundred and fifty-seven studies were found, and 23 were selected based on the eligibility criteria. The articles presented were conclusive in determining the importance of the number of axons in the success of nerve transfer. Still, the relationship between the number of axons in the donor and recipient nerves seems more relevant in the success of transfers and is not always explored by the authors. The review of the articles has provided compelling evidence that the number of axons is a critical determinant of the success of nerve transfer procedures. However, the relationship between the number of axons in the donor nerve and that in the recipient nerve appears to be even more crucial for successful transfers, a factor that is not always adequately explored by authors in the existing literature.Level of evidence: Level IV, therapeutic study
Keywords: axon count; nerve transfer; systematic review; donor and recipient nerve.